The performance of phenol biodegradation by candida tropicalis retl-Cr1 using batch and fed-batch fermentation techniques [electronic resource] - 353288 Piakong Mohd. Tuah (2006)
Thesis (Doctor of Philosophy) - Universiti Teknologi Malaysia, 2006